ЕКОЛОГІЧНИЙ ПІДХІД ДО ЗБЕРЕЖЕННЯ СІЛЬСЬКОГОСПОДАРСЬКИХ РОСЛИН НА ПРИКЛАДІ TRITICUM AESTIVUM L.: МОРФОМЕТРИЧНІ, ФІЗІОЛОГІЧНІ ТА БІОХІМІЧНІ РЕАКЦІЇ (Ecological Bulletin of Kryvyi Rih District, 2025)
Having the ability to organise a programme of their individual development depending on the prevailing cultivation conditions, the adaptive response of plants to stress includes changes in regulatory and metabolic structures, the level of interconnections of which combines different types of adaptive reactions. Recently, the development of biotechnological methods has made it possible to determine which characteristics change in response to a particular stress and has shown that genetic control of adaptation mechanisms to various types of adverse effects is a complex system of signal transduction pathways and regulatory factors.  Recently, the development of plant forms with an increased level of osmotolerance to osmotic stresses has been associated with the use of biotechnological methods. An important role in maintaining plant osmotolerance belongs to free proline, which is one of the most multifunctional stress metabolites in plants. The germination of seeds under simulated water stress was studied. Stress was created by 0.5 M and 0.8 M mannitol solution. In the presence of mannitol, a decrease in the number of seedlings was observed in all tested variants. At the same time, genotypic differences were observed. To study the salt tolerance, the seeds were germinated for 10 days in a 0.5 diluted Murashige-Skoog solution with the addition of 20.0 and 25.0 g/l of seawater salts. On day 10, the content of free proline in the leaves of young plants was analysed. An increase in the level of proline was observed in response to salt stress. Genotypic differences were observed in the degree of the reaction. The nature of the accumulation of free proline under normal and stressful conditions provides evidence in favour of the functioning of the plant gene. Under osmotic stress, the level of free proline increases as a result of synthesis. These genotypic features may indicate an indirect effect on the endogenous genes of the plant. At the initial stages of research, the stress-response relationship can be established by changing the conditions of stress and recovery.  The fundamental role of proline in osmotic regulation and increasing the ability of plants to withstand cell dehydration caused by salinity, drought or extreme temperatures is well understood.
Keywords: proline, winter wheat, growth parameters, soil drought, osmotic resistance